2019
DOI: 10.3389/fmats.2019.00104
|View full text |Cite
|
Sign up to set email alerts
|

A Simple “Nano-Templating” Method Using Zeolite Y Toward the Formation of Carbon Schwarzites

Abstract: Schwarzites have a three-dimensional sp 2 carbon structure with negative Gaussian curvatures. They can be synthesized through the deposition of carbon by chemical vapor deposition on a zeolite template and may be formed by increasing the amount of carbon. In this research, the amount of carbon deposition was increased by shortening the length of the diffusion pathways of the template through the use of nano-sized zeolite Y (nano-FAU). It was found that significantly larger quantities of carbon could be deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…These materials have been used for cleaning up polluted water; plastic wastes and biomass gasification residues to chars and activated carbon are also attracting a lot of attention (Bazargan et al, 2013;Benedetti et al, 2019). Of late, some new adsorbent materials such as graphenes (Kyzas et al, 2018;Abu-Nada et al, 2020), carbon nanotubes (Gupta et al, 2013), MCM-41 (Lam et al, 2007), schwartzites (Boonyoung et al, 2019) have also been reported in the literature as high capacity adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have been used for cleaning up polluted water; plastic wastes and biomass gasification residues to chars and activated carbon are also attracting a lot of attention (Bazargan et al, 2013;Benedetti et al, 2019). Of late, some new adsorbent materials such as graphenes (Kyzas et al, 2018;Abu-Nada et al, 2020), carbon nanotubes (Gupta et al, 2013), MCM-41 (Lam et al, 2007), schwartzites (Boonyoung et al, 2019) have also been reported in the literature as high capacity adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of molecular simulations, it was recently proposed that the structure of the ZTC forming within larger zeolite crystals would differ (less dense structure) to that developing within small crystals (denser structure). 15 The authors compared zeolite crystals of 40 vs. 300 nm, which might not present a sufficiently important size difference to observe a real impact of the crystal size on structural quality. Indeed, independently of the crystal size ethylene does not face diffusion limitations in large pore zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time TPMSs remained quite abstract objects; however, in the last few years, they have attracted great interest as models for potential porous materials possessing valuable physical properties (Park & Lee, 2019;Zheng et al, 2018), or playing a template role in chemical syntheses (Braun et al, 2018;Boonyoung et al, 2019) and manufacturing of metamaterials (Al-Ketan & Abu Al-Rub, 2019). However, no methods for the comprehensive generation of TPMSs have been proposed and the practical applications mainly rest upon several TPMSs for which the analytical functions are known, in particular, primitive (P), diamond (D) and gyroid (G) surfaces (Abueidda et al, 2017;Maskery et al, 2018).…”
Section: Introductionmentioning
confidence: 99%